Decision-makings of individual innovative behaviors in different educational settings: a case study of university student innovation competitions in China - Feng, Jiao; Sun, Guoshuai (Frontiers in Psychology, 2025)
IntroductionWith the intensification of global competition and rapid technological advancement, fostering innovation capabilities among university students has become a focal point of attention across society. However, within higher education environments, various contextual factors may exert direct or indirect influences on students’ motivation and effectiveness in implementing individual innovative behaviors.MethodsTo address this issue, the present study takes the rapid rise of university student innovation competitions in China as a background case and adopts a dual perspective from social psychology and educational psychology. A tripartite evolutionary game model is developed, involving individual students, universities, and competition organizers. The model is designed to examine how students make strategic decisions regarding innovation under varying contextual influences, and how these decisions are shaped by the actions of universities and organizers.ResultsThe findings reveal that supportive educational policies, innovation-oriented campus cultures, and well-designed competition incentive mechanisms significantly enhance students’ motivation and the effectiveness of their innovative efforts. Moreover, strategic support from universities and organizers plays a critical role in sustaining students’ long-term engagement in innovation activities.DiscussionBy integrating psychological theories with evolutionary game modeling, this study provides novel insights into how contextual interactions shape individual innovation behavior. The results offer practical implications for optimizing educational environments and provide evidence-based guidance for policymakers and educators aiming to foster student-led innovation.